Immobilization of Tungsten Oxide (WO3) Material on Glass Substrate Using the Direct Spray Deposition (DSD) Method - Iqbal Firdaus; Hendri Widyandari; Pulung Karo Karo; Rana Yuliandra; Yusril Al Fath (Journal of Energy, Material, and Instrumentation Technology, 2026)
Tungsten oxide (WO3) is a semiconductor material with promising potential for photocatalytic applications due to its visible-light response and good chemical stability. In this study, WO3 films were successfully immobilized on glass substrates using a combination of photodeposition and Direct Spray Deposition (DSD) methods. The precursor solution was prepared from ammonium paratungstate, followed by photodeposition under visible-light irradiation and deposition onto heated glass substrates using the DSD technique. The deposited films were annealed at temperatures of 500 degC, 600 degC, and 650 degC. Structural characterization was performed using X-Ray Diffraction (XRD), while surface morphology was analyzed using Scanning Electron Microscopy (SEM). XRD results revealed that increasing the annealing temperature improved the crystallinity of the films and induced phase transformations from W5O14 to W25O73 and W18O49 phases. SEM observations showed that higher annealing temperatures produced denser and more uniform film surfaces, with plate-like morphologies clearly observed at 650 degC. These findings demonstrate that annealing temperature strongly influences the structural and morphological characteristics of WO3 films prepared by the DSD method.